Penerapan Status Pengguna Pada Tindak Pidana Narkotika Dalam Prespektif Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika - Montana Maruli Pakpahan; Erwin Owan Hermansyah; Lukman Hakim (Jurnal Hukum Sasana, 2021)
The aim of the author examines the application of imprisonment for a narcotics user and optimizes the provision of rehabilitation rights for narcotics users from the perspective of Law Number 35 of 2009 concerning Narcotics, is to describe the extent to which sentences for narcotics users are applied and what penalties are in accordance with statutory regulations in Indonesia and how to optimize the provision of rehabilitation rights for narcotics users in Indonesia and what are the obstacles in granting rehabilitation rights. This type of research is a normative juridical legal research with descriptive characteristics derived from primary law and secondary legal materials. Secondary data includes primary legal materials, secondary legal materials and tertiary materials collected by means of literature studies. The data is compiled in the form of a description and then analyzed qualitatively, meaning that the data is interpreted and discussed based on theories (doctrines) and the principles and legal regulations relating to the subject matter. The implementation of prison terms for a user is not sufficiently in accordance with the perspective of Law Number 35 of 2009 concerning Narcotics because Law Number 35 of 2009 concerning Narcotics regulates the right to rehabilitation for narcotics users, namely placing narcotics abusers / users into rehabilitation institutions through a judge's decision. because this is a very good alternative to the provision of criminal sanctions in terms of deferent aspect and refresh aspect. However, the implementation of rehabilitation rights for narcotics users in Indonesia has not been optimal due to several obstacles, both from internal, external and legal regulations, which make narcotics users often given imprisonment penalties rather than rehabilitation crimes.